Effect of combined electrostimulation and plyometric training on vertical jump height - Maffiuletti, N. A.; Dugnani, S.; Folz, M.; Di Pierno, E.; Mauro, F. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: This study investigated the influence of a 4-wk combined electromyostimulation (EMS) and plyometric training program on the vertical jump performance of 10 volleyball players. METHODS: Training sessions were carried out three times weekly. Each session consisted of three main parts: EMS of the knee extensor muscles (48 contractions), EMS of the plantar flexor muscles (30 contractions), and 50 plyometric jumps. Subjects were tested before (week 0), during (week 2), and after the training program (week 4), as well as once more after 2 wk of normal volleyball training (week 6). Different vertical jumps were carried out, as well as maximal voluntary contraction (MVC) of the knee extensor and plantar flexor muscles. RESULTS: At week 2, MVC significantly increased (+20% knee extensors, +13% plantar flexors) as compared to baseline ( < 0.05). After the 4-wk training program, different vertical jumps considered were also significantly higher compared to pretraining ( < 0.001), and relative gains were comprised between 8-10% (spike-counter movement jump) and 21% (squat jump). The significant increases in maximal strength and explosive strength produced by the present training program were subsequently maintained after an additional 2 wk of volleyball training. CONCLUSION: EMS combined with plyometric training has proven useful for the improvement of vertical jump ability in volleyball players. This combined training modality produced rapid increases (approximately 2 wk) of the knee extensors and plantar flexors maximal strength. These adaptations were then followed by an improvement in general and specific jumping ability, likely to affect performance on the court. In conclusion, when EMS resistance training is proposed for vertical jump development, specific work out (e.g., plyometric) must complement EMS sessions to obtain beneficial effects.